Thermal hydrolyzed food waste liquor as liquid organic fertilizer - Gao, Shumei (2022)
Thermal hydrolysis (TH) is an efficient technology for food waste (FW) management. This study investigated the nutrients released from FW under various TH temperature (140, 160, 180, 200 and 220 °C) and evaluated the feasibility of the hydrolyzed liquor (HL) as liquid organic fertilizer. The phytotoxicity and biotoxicity of HL was analyzed using wheat seed and Pseudomonas putida. Results revealed that TH could effectively solubilize FW and release nutrients (N, P and K) and organic substances. The highest content of total nitrogen (TN, 1685 mgN/L) and phosphorus (TP, 235 mgP/L) in the HL was obtained under 180 °C. The K+ was 278-293 mg/L regardless of treatment temperature. Secondary nutrients (Ca and Mg) and micro metals (Fe, Cu, Zn, Al, Co and Mn) were all detected at relatively high level, while heavy metals (As and Cd) were generally lower than 0.5 mg/L. Twenty types of free amino acid were identified and the maximum total concentration was 4965.13 mg/L. 2% HL displayed higher germination index (>80%) and enhanced root and shoot lengths. No biotoxicity was observed as confirmed by the bioassay. This study proposes a feasible method to solubilize food waste and produce liquid organic fertilizer.